2020
DOI: 10.18510/ijthr.2020.716
|View full text |Cite
|
Sign up to set email alerts
|

Building a Heritage Tourism Development Blueprint for Bangladesh: An Explorative Investigation

Abstract: Purpose of the study: Bangladesh is blessed with all the possibility to be an imperative heritage destination on global premises, whereas there are a number of obstacles that can obstruct the effective development of the heritage tourism segment in the country. As a result, the present study targets to explore major issues that are critical in the development process of heritage tourism. Methodology: The study has organised 25 semi-structured interview procedures for data collection. The respondents are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…While, in the case of Bangladesh, several studies have explored heritage focusing on the identification, representation, existing situation or vulnerabilities of heritage ( Islam and Wahab, 2020 ; Khalid and Chowdhury, 2018 ), community-based heritage tourism ( Sharmin and Hossain, 2020 ). No significant research has been found in Bangladesh, where community engagement and public education has emphasized heritage conservation.…”
Section: Introductionmentioning
confidence: 99%
“…While, in the case of Bangladesh, several studies have explored heritage focusing on the identification, representation, existing situation or vulnerabilities of heritage ( Islam and Wahab, 2020 ; Khalid and Chowdhury, 2018 ), community-based heritage tourism ( Sharmin and Hossain, 2020 ). No significant research has been found in Bangladesh, where community engagement and public education has emphasized heritage conservation.…”
Section: Introductionmentioning
confidence: 99%